Bardet-Biedl Syndrome: A Case Report (Journal of Dhaka Medical College, 2024)
Bardet-Biedl syndrome (BBS) is a rare autosomal recessive multisystem involvement genetic disorder with a broad spectrum of clinical presentations. It is characterized by rod-cone dystrophy, polydactyly, obesity, learning disabilities, hypogonadism in males or genital abnormalities in females, and renal impairment. We present a case of a 12-year-old boy who complained of gradual loss of vision (particularly noticeable at night), obesity, hypogenitalism, and polydactyly. In addition, he had postaxial polydactyly in all limbs, obesity, retinitis pigmentosa, learning disabilities, hypogenitalism, speech delay, developmental delay, astigmatism, and acanthosis nigricans. Multidisciplinary approaches need to manage this disorder and need regular followup. Genetic counselling is essential.J Dhaka Med Coll. 2022; 31(2) : 264-267